Photocatalytic inactivation of diarrheal viruses by visible-light-catalytic titanium dioxide - Xiaojie Sang (2018)
Titanium dioxide (TiO2) that had been irradiated with visible light (VL) was demonstrated to inactivate rotavirus, astrovirus, and feline calicivirus (FCV). The virus titers were dramatically reduced after exposure for 24 hrs to the VL-catalytic TiO2. The addition of bovine serum albumin could protect the virus against inactivation by VL-catalytic TiO2 in a dose-dependent manner. This finding implied that the VL-catalytic TiO2 products might somehow interact initially with the viral proteins in the process of virus inactivation. Moreover, we showed partial degradation of the rotaviral dsRNA genome. This was more prominent when the virus was exposed to the VL-catalytic TiO2 treatment for at least 2 days. An attempt was made to elucidate the mechanism underlying the inactivation of the viruses. It was found that upon activation of TiO2 with VL by using a white fluorescent lamp, the reactive oxygen species such as superoxide anions (O2) and hydroxyl radicals (·OH) were generated in a significant amount after stimulation for 8, 16, and 24 hrs. We therefore assume that virus inactivation by VL-catalytic TiO2 might occur through the generation of O2 and ·OH followed by damage to the viral protein and genome. This is the first report, to the best of our knowledge, demonstrating the inactivation of rotavirus, astrovirus and FCV by the presence of TiO2 film under VL as well as describing its mechanism.